Aplikasi Kultur Jaringan dalam Pemeliharaan Bibit Rumput Laut Kappaphycus alvarezii di Laboratorium BPBL Ambon - Mainassy, Meillisa Carlen; Asinado Hutabalian1; Madellayne Glosallya Ririmasse; Meylany Songjanan (Komunikasi, 2025)
This community service activity aimed to apply tissue culture techniques for developing high-quality seedlings of Kappaphycus alvarezii (Cotoni seaweed) at the Marine Aquaculture Center (BPBL) Laboratory in Ambon. The methods involved the preparation of solid and liquid PES-based media, sterilization of tools and materials, and maintenance of micropropagules and plantlets under aseptic conditions. Observations focused on media quality, plantlet growth, and subculture frequency. Results showed that P2.5NW1PW1T and SM FITO media supported optimal plantlet development with low mortality rates, while media with high hormone concentrations induced plantlet death. The findings emphasize the importance of media formulation and water quality monitoring in tissue culture success. This program demonstrated a practical contribution to the sustainable cultivation technology of seaweed aquaculture.